Research progress of standardized management of pain in chronic wounds (慢性伤口规范化疼痛管理的研究进展) - YUE Lina (岳丽娜); LI Jinghuan (李靖嬛) (中西医结合护理)
Chronic wound nursing has always been a thorny issue in the process of wound treatment, and pain is a common symptom of chronic wounds. Management of pain in chronic wounds is related to patients’ treatment compliance and affects the wounds healing. This article briefly described the current situation of standardized pain management in chronic wounds, in order to provide ideas for standardized management of pain in chronic wounds. (慢性伤口护理是伤口治疗过程中比较棘手的问题。疼痛是慢性伤口常见症状, 慢性伤口疼痛管理质量和患者治疗依从性密切相关, 影响着伤口的愈合速度。本文简述慢性伤口规范化疼痛管理的现状, 以期为慢性伤口规范化疼痛管理提供思路。)